How differences in perceptions of own and team performance impact trust and job satisfaction in virtual teams. Issue 4 (7th August 2016) - Romeike, Philipp Daniel; Nienaber, Ann-Marie; Schewe, Gerhard
ABSTRACT: Employees frequently engage in social comparison processes and tend to perceive their own performance as superior compared to that of their peers. We expect this to be particularly salient in virtual teams where employees receive few cues upon which the comparison with other members of their team can be based. With reliance on social comparison and social exchange theory, we propose that such "perceived overperformance" has negative effects on job satisfaction, which is mediated by trust in the team. We confirm this with a sample of field-service employees ( n  = 753) using structural equation modeling with bootstrapping. We corroborated our findings in focus groups, which suggest the need for performance indicators that are easily communicated to and comprehended by employees to maintain trust and satisfaction.